A relational study on service quality of contact centre representatives in Klang Valley - Azlina, Omar (2014)
Contact centre industries in Malaysia are growing and the rate of growth is tremendously encouraging. With the growth rate, Malaysia has been recognized as the new Asia Pacific Contact Centre Hub. The employment among local will increased aligned with the initiative of international; global organization to locate their contact centre here, in Malaysia. However, previous statistics showed that the turnover rates in this industry is high and increasing throughout Asia. As such, human capital management are crucially important in view to ensure the successful of the contact centres. To compete with other global contact centres, Malaysian contact centres should be ready to strive and compete with an international contact centres. Indeed, it is critical for a contact centre management to effectively follow the course of strategic success factors in term of contact centre human capital management. This research was conducted with a target to explore how service quality in the Malaysian contact centres associates to the behaviour of a contact centre representatives, in view of representative's work motivation, work climate and organizational commitment. A survey method was used in the research. Two hundred and eighty survey forms were distributed within five financial institutions contact centres in Malaysia. The results of the survey were analysed by using the SPSS programme. The results of the analysis found that the service quality in contact centres are significantly related to the contact centre representatives work climate and organizational commitment. However, the results found that the service quality in contact centres was not statistically significant related to the contact centre representatives work motivation. The study also revealed that there is no differences between gender and service quality within contact centre representatives in Klang Valley